Boosting Output Performance of Triboelectric Nanogenerator via Mutual Coupling Effects Enabled Photon‐Carriers and Plasmon - Xin Chen; Yanjun Zhao; Fayang Wang; Daqiao Tong; Lingxiao Gao; Dongxiao Li; Liangke Wu; Xiaojing Mu; Ya Yang (Advanced Science, 2022)
Abstract Boosting the output performance of triboelectric nanogenerators via some unique methods is always a meaningful way to speed up their commercialization. However, the available approach to boost performance is mainly restricted to one physics effect based and the basic research of boosting performance via mutual coupling effects is little research. Herein, a new strategy is creatively proposed based on charge traps from mutual coupling effects, generated from g‐C3N4/MXene‐Au composites, to further promote the output performance of triboelectric nanogenerator. It is found that photon‐generated carriers coupling surface plasmon effect enables composites filled into tribo‐material with visible light is an excellent value in boosting performance. The charge traps from mutual coupling effects for boosting performance are analyzed theoretically and verified by experiments. The output power of boosting‐triboelectric nanogenerator (TENG) achieves a sixfold enhancement (20 mW) of normal TENG with polydimethylsiloxane (PDMS) in ambient conditions. This work provides a profound understanding of the working mechanism of mutual coupling effects boosting the performance of TENG and an effective way for promoting TENG output.